Alternating hemiplegia of childhood: An electroclinical study of sleep and hemiplegia. - Josephine Poole; Sara Zagaglia; Rita Demurtas; Fiona Farrell; Matthew C Walker; Sanjay M Sisodiya; Simona Balestrini; Umesh Vivekananda (PLoS ONE)
Objective Alternating Hemiplegia of Childhood (AHC) is characterised by paroxysmal hemiplegic episodes and seizures. Remission of hemiplegia upon sleep is a clinical diagnostic feature of AHC. We investigated whether: 1) Hemiplegic events are associated with spectral EEG changes 2) Sleep in AHC is associated with clinical or EEG spectral features that may explain its restorative effect. Methods We retrospectively performed EEG spectral analysis in five adults with AHC and twelve age-/gender-matched epilepsy controls. Five-minute epochs of hemiplegic episodes and ten-minute epochs of four sleep stages were selected from video-EEGs. Arousals were counted per hour of sleep. Results We found 1) hemispheric differences in pre-ictal and ictal spectral power (p = 0.034), during AHC hemiplegic episodes 2) 22% reduced beta power (p = 0.017) and 26% increased delta power (p = 0.025) during wakefulness in AHC versus controls. There were 98% more arousals in the AHC group versus controls (p = 0.0003). Conclusions There are hemispheric differences in spectral power preceding hemiplegic episodes in adults with AHC, and sleep is disrupted. Significance Spectral EEG changes may be a potential predictive tool for AHC hemiplegic episodes. Significantly disrupted sleep is a feature of AHC.